2016
DOI: 10.11607/ijp.4835
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Dimensional Accuracy of 3D-Printed Full-Coverage Dental Restorations Using Stereolithography Technology

Abstract: The aim of the present study was to evaluate the effect of the build angle and the support configuration (thick versus thin support) on the dimensional accuracy of 3D-printed full-coverage dental restorations. Materials and Methods: A full-coverage dental crown was digitally designed and 3D-printed using stereolithography-additive manufacturing (SLA-AM) technology. Nine different angles were used during the build process: 90, 120, 135, 150, 180, 210, 225, 240, and 270 degrees. In each angle, the crown was prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
186
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(197 citation statements)
references
References 16 publications
6
186
1
4
Order By: Relevance
“…Similarly, it has been proposed that the adhesion between successive layers is weaker than the adhesion within the same layer 12 , which is partly true and especially dependent upon the conditions at which polymerization occur, as we have also observed (supplementary figure S1). Alharbi et al 15 showed that a 3D printed interim dental material (Temporalis, DWS), similar to the one we tested here, had higher compressive strength when printed in a 90° orientation than when printed in a 0° orientation. The authors observed that uniaxial compression of the sample led to several microcracks, which appeared to propagate from main cracks formed between layers.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, it has been proposed that the adhesion between successive layers is weaker than the adhesion within the same layer 12 , which is partly true and especially dependent upon the conditions at which polymerization occur, as we have also observed (supplementary figure S1). Alharbi et al 15 showed that a 3D printed interim dental material (Temporalis, DWS), similar to the one we tested here, had higher compressive strength when printed in a 90° orientation than when printed in a 0° orientation. The authors observed that uniaxial compression of the sample led to several microcracks, which appeared to propagate from main cracks formed between layers.…”
Section: Discussionsupporting
confidence: 73%
“…Samples set to the same dimensions of our printable resins but printed using a control clear resin provided by the printer manufacturer showed outstanding precision (data not shown). Similarly, Alharbi et al reported provisional crowns 3D printed using a 3D printer from the same manufacturer as the dental material itself with a printing accuracy down to 30 μm of the CAD designs 15 . In summary, it remains to be tested whether the values obtained with our 3D printing system and material are comparable to results obtained using conventional protocols for manual provisional crown and bridge restorations.…”
Section: Discussionmentioning
confidence: 99%
“…These reasons are confirmed in a study that showed that the dimensional accuracy of the PEEK varied depending on the mold temperature and specimen depth, and expansion of approximately 33% from the original dimension of 0.8 mm and an approximately 32% in the case of the 1‐mm depth of the thermo‐pressed specimen was noted at 200°C . This finding also could be due to the selected build angle (90°) with thick support used during printing of the resin pattern, which might have affected the dimensional accuracy of the resin pattern and subsequently affected the overall accuracy . When interpreting the accuracy of fit, it has to be borne in mind that a misfit with space from the reference cast results in a positive value (red), and compression of the tissues is indicated by negative values (blue).…”
Section: Discussionmentioning
confidence: 99%
“…24 This finding also could be due to the selected build angle (90°) with thick support used during printing of the resin pattern, which might have affected the dimensional accuracy of the resin pattern and subsequently affected the overall accuracy. 25 When interpreting the accuracy of fit, it has to be borne in mind that a misfit with space from the reference cast results in a positive value (red), and compression of the tissues is indicated by negative values (blue). Thus, calculating the mean value might have neutralized the spacing and compression zones in some areas.…”
Section: Discussionmentioning
confidence: 99%
“…These variations may have occurred because tibia geometry at the proximal-medial site was relatively at. Additionally, the small RMS error may be related to the 3Dprinting build orientation with a 90° build angle and thick support structure [25,26]. These results indicate that the data acquisition method, bone size and geometry, manufacturing process, and material could all have in uenced the accuracy of the nal model.…”
Section: Discussionmentioning
confidence: 92%